Unearthing Nusantara’s Concept of Religious Pluralism: Harmonization and Syncretism in Hindu-Buddhist and Islamic Classical Texts - Al Makin (Al-Jami'ah Research Centre, 2016)
This article sheds light on the formulation of pluralism based on the reading of classical Javanese texts by choosing some excerpts of Hindu-Buddhist literature called kakawin and later Islamic works called serat and babad. Dynamic practices of syncretism and harmonization of local and foreign religious traditions are found in the excerpts of Sutasoma, Kertagama, Dewa Ruci, Babad Tanah Jawa, and Centini. From reading of these messages, this writing finds that since the old time of Singasari and Majapahit, harmonization and syncretism of many religious traditions has been practiced as an essential part of the concept of pluralism. Hindu-Buddhist came first in the older literature and later Islamic elements added the complexity of syncretism. This study also finds that Hindu-Buddhist figures are reenacted in the Islamic literature with modifications. The accounts of the famous Javanese saint Sunan Kalijaga reflects the older source of Sutasoma, Ken Arok, Bhima, and other figures. Their stories tell us about the relativism of evil and good, in which evil is not annihilated but converted into goods. This article is an example of our endeavor that pluralism can be formulated based on local wisdom such as reading classical texts with the spirit of reinterpretation of indigenous virtues with a fresh perspective.[Artikel ini mencoba menemukan rumusan pluralisme dengan membaca ulang teks klasik Jawa dengan memilih bagian tertentu dari sastra Hindu-Buddha yang disebut kakawin dan karya Islami yang disebut serat dan babad. Praktik dinamis sinkretisme dan penyelarasan antara tradisi keagamaan lokal dan asing ditemui dalam Sutasoma, Kertagama, Dewa Ruci, Babad Tanah Jawa, dan Centini. Dari hasil bacaan teks-teks di atas, tulisan ini menemukan bahwa sejak masa kuno Singasari dan Majapahit, penyelarasan dan sinkretisme antara banyak tradisi keagamaan telah dipraktikkan sebagai bagian penting dari konsep pluralisme. Hindu-Buddha datang pertama lalu disusul oleh karya Islam yang menambah nuansa sinkretis. Studi ini juga menemukan bahwa tokoh Hindu-Buddha diceritakan ulang dalam karya Islam dengan berbagai modifikasi. Cerita tentang Sunan Kalijaga mencerminkan sumber yang lebih tua seperti Sutasoma, Ken Arok, Bhima, dan tokoh-tokoh lain. Kisah mereka mengajarkan kepada kita tentang relativitas antara kejahatan dan kebaikan; kejahatan tidak dimusnahkan tetapi diubah menjadi kebaikan. Artikel ini merupakan contoh usaha untuk merumuskan konsep pluralisme berdasarkan kebijakan lokal dengan membaca kembali teks-teks klasik dengan semangat penafsiran ulang ajaran lokal dengan perspektif baru.]